Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1210/jc.2002-020106
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol and Interleukin-1β Exert a Synergistic Stimulatory Effect on the Expression of the Chemokine Regulated upon Activation, Normal T Cell Expressed, and Secreted in Endometriotic Cells

Abstract: Endometriosis, commonly associated with intraperitoneal inflammation, is estrogen dependent. Possible links between the immunoinflammatory and endocrine changes observed in endometriotic women have been poorly understood. In this study, we report that estradiol (E(2)) and IL-1beta exert a synergistic stimulatory action on RANTES (regulated upon activation, normal T cell expressed, and secreted) expression by endometriotic cells. Treatment of endometriotic cells with IL-1beta had a dose-dependent effect on RANT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 38 publications
3
46
0
Order By: Relevance
“…The inhibitory activity of IL-1ra was even shown to be enhanced by soluble IL-1RII and hindered by soluble IL-1RI (Burger et al 1995). According to our and other previous data, endometriotic cells are highly sensitive and responsive to IL-1 (Akoum et al 1995(Akoum et al , 2000(Akoum et al , 2002, and secrete increased levels of angiogenic factors compared with endometrial cells from normal women (Lebovic et al 2000). Also, IL-1RI is, in contrast to the decoy inhibitory IL-1RII, slightly released in the culture medium of endometrial and endometriotic cells (personal data).…”
Section: Il-1ri Expression In Ectopic Endometrial Tissuesupporting
confidence: 68%
See 2 more Smart Citations
“…The inhibitory activity of IL-1ra was even shown to be enhanced by soluble IL-1RII and hindered by soluble IL-1RI (Burger et al 1995). According to our and other previous data, endometriotic cells are highly sensitive and responsive to IL-1 (Akoum et al 1995(Akoum et al , 2000(Akoum et al , 2002, and secrete increased levels of angiogenic factors compared with endometrial cells from normal women (Lebovic et al 2000). Also, IL-1RI is, in contrast to the decoy inhibitory IL-1RII, slightly released in the culture medium of endometrial and endometriotic cells (personal data).…”
Section: Il-1ri Expression In Ectopic Endometrial Tissuesupporting
confidence: 68%
“…IL-1 would have more pronounced effects on adhesion in endometriosis (Sillem et al 1999). Activation and recruitment of immune cells into endometriotic implants can be mediated by other secreted cytokines and chemokines such as MCP-1, RANTES, IL-6, and IL-8, which were found to be up-regulated by IL-1 in endometriotic cells (Akoum et al 1995(Akoum et al , 1996(Akoum et al , 2002) and could in turn promote IL-1 secretion by activated immune cells. IL-1 induces secretion of IL-8 and IL-6, which exhibit proangiogenic properties (Akoum et al 1996.…”
Section: Il-1ri Expression In Ectopic Endometrial Tissuementioning
confidence: 99%
See 1 more Smart Citation
“…MCP-1 and RANTES are well-known chemokines whose concentrations are high in peritoneal fluid of women with endometriosis 61,62 and whose secretions are promoted by estrogen. 34,35 In human endometriotic stromal cells, inflammatory stimuli induce secretion of these chemokines, and estrogen enhances their secretion. 34,35 In vitro studies in human endometrial stromal cells have shown that adding P 4 does not suppress estrogen-induced expression of these chemokines, 34,35 suggesting P 4 resistance in endometriotic cells.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 In human endometriotic stromal cells, inflammatory stimuli induce secretion of these chemokines, and estrogen enhances their secretion. 34,35 In vitro studies in human endometrial stromal cells have shown that adding P 4 does not suppress estrogen-induced expression of these chemokines, 34,35 suggesting P 4 resistance in endometriotic cells. Our present findings that Fkbp52 null mice with endometriotic lesions have enhanced levels of chemokines in their peritoneal fluids corroborates well with reduced PR and FKBP52 expression and unchanged ER␣ expression in ectopic lesions.…”
Section: Discussionmentioning
confidence: 99%